PEMANFAATAN MEDIA POWTOON DALAM KEGIATAN KETERAMPILAN BERBAHASA - Tambunan, Marlina Agkris; Sidabutar, Yanti Arasi; Br. Gultom, Meliana; Silitonga, Immanuel D.B; Sihombing, Berliana (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2025)
Amidst the rapid technological developments in the current digital era, the world of education is required to adapt to the use of technology-based media to support the learning process. One potential media to be used is Powtoon, an interactive and engaging animation platform, highly relevant to support language skills activities. In facing the flow of disruptive innovation in the Industrial Revolution 4.0 era, educators need to improve their competencies, especially in the use of innovative and flexible learning technology. This community service activity was carried out through an educational approach, training, and direct mentoring to the participants. The stages of the activity include: 1) Providing education related to digital literacy and an introduction to the Powtoon application, 2) Training in creating animation-based learning content (starting from the planning stage, making practice, to presenting the results), and 3) Mentoring and measuring participants' mastery of the media. The target of this activity is teachers at SD 091537 Hutabayu, Simalungun Regency. The activity was attended by 5 lecturers from various disciplines (Indonesian, PGSD, German, and English) and 1 student from the Indonesian Language Education Study Program. Based on the evaluation results, 90% of participants stated that this activity was very helpful and provided new insights regarding the use of Powtoon in language learning, while another 10% stated that this activity was useful and relevant to current learning needs.